2021
DOI: 10.3389/fenrg.2021.671279
|View full text |Cite
|
Sign up to set email alerts
|

Remote Renewable Hubs for Carbon-Neutral Synthetic Fuel Production

Abstract: This paper studies the economics of carbon-neutral synthetic fuel production from renewable electricity in remote areas where high-quality renewable resources are abundant. To this end, a graph-based optimisation modelling framework directly applicable to the strategic planning of remote renewable energy supply chains is proposed. More precisely, a hypergraph abstraction of planning problems is introduced, wherein nodes can be viewed as optimisation subproblems with their own parameters, variables, constraints… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…At present, most of the research related to carbon neutrality at home and abroad focus on new technologies and energy transition, for example, the improvement of cryogenic energy storage technology needed in the process of carbon neutralization in the refrigeration and power supply industry [53], the development of biofuel production technology in the European Union [54], the carbon-neutral transformation planning study of the power system in New York [55], the evaluation study of the carbon neutral potential of CO 2 removal in Europe [56], the realization method study of a carbon neutral campus [57], and the carbon-neutral and livable health and urban transportation planning path [58]. Most research in China is also focused on carbon-neutral technologies and energy transition [59].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most of the research related to carbon neutrality at home and abroad focus on new technologies and energy transition, for example, the improvement of cryogenic energy storage technology needed in the process of carbon neutralization in the refrigeration and power supply industry [53], the development of biofuel production technology in the European Union [54], the carbon-neutral transformation planning study of the power system in New York [55], the evaluation study of the carbon neutral potential of CO 2 removal in Europe [56], the realization method study of a carbon neutral campus [57], and the carbon-neutral and livable health and urban transportation planning path [58]. Most research in China is also focused on carbon-neutral technologies and energy transition [59].…”
Section: Discussionmentioning
confidence: 99%
“…83 Because a DAC facility can provide on-site CO 2 generation anywhere, its application is advantageous in addition to its environmental benefits. Recently, the potential application of adsorption-based DAC in indoor air removal, 115,191,193,208,209 CO 2 fertilization, 178,210 biomass production, [211][212][213][214][215] fuel production (CH 4 , 68,70,75,[216][217][218][219][220][221][222] methanol, 71,[223][224][225][226] aviation fuel, 73,[227][228][229][230][231][232] hydrocarbons 233 ), chemicals (Fischer-Tropsch process, 234,235 carbon nanotubes, 236 dimethyl carbonate, 237 syngas 238,239 ), mineralization, [240][241][242][243][244] storage, 245,246 enhanced oil recovery (EOR), …”
Section: Overview Of Adsorption-based Dac Technologiesmentioning
confidence: 99%
“…71,217,220,226,230 Emphasis was also given to the cost of using different renewable energies and the inflexibility of processes, such as DAC, water desalination, and fuel synthesis. Berger et al 219 studied methane production in North Africa using a combination of solar and wind energy as well as its delivery to northwestern European markets. Sensitivity analysis showed that the full electricity supply from solar PV was more expensive than that in the combination case.…”
Section: Reported Amentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the low local demand, exploiting the renewable energy potential of a remote resource-ful area allows a large part of the generated electricity to be directly exported to high-demanding regions. Secondly, the concept of "remote renewable hubs" suggests that this electricity could be used to produce on-site carbon-neutral synthetic fuels that are then to be exported as well to highdemanding regions, as discussed in Berger et al (2021).…”
Section: Introductionmentioning
confidence: 99%